The IGF2 intronic miR-483 selectively enhances transcription from IGF2 fetal promoters and enhances tumorigenesis - Liu, Mingzhu; Roth, Anna; Yu, Min; Morris, Robert; Bersani, Francesca; Rivera, Miguel N.; Lu, Jun; Shioda, Toshihiro; Vasudevan, Shobha; Ramaswamy, Sridhar; Maheswaran, Shyamala; Diederichs, Sven; et al. (Genes & development, 2013)
Insulin-like growth factor 2 (IGF2), a developmentally regulated and maternally imprinted gene, is frequently overexpressed in pediatric cancers. Although loss of imprinting (LOI) at fetal promoters contributes to increased IGF2 in tumors, the magnitude of IGF2 expression suggests the involvement of additional regulatory mechanisms. A microRNA (miRNA) screen of primary Wilms' tumors identified specific overexpression of miR-483-5p, which is embedded within the IGF2 gene. Unexpectedly, the IGF2 mRNA itself is transcriptionally up-regulated by miR-483-5p. A nuclear pool of miR-483-5p binds directly to the 5′ untranslated region (UTR) of fetal IGF2 mRNA, enhancing the association of the RNA helicase DHX9 to the IGF2 transcript and promoting IGF2 transcription. Ectopic expression of miR-483-5p in IGF2-dependent sarcoma cells is correlated with increased tumorigenesis in vivo. Together, these observations suggest a functional positive feedback loop of an intronic miRNA on transcription of its host gene.